The endemic element of the Chihuahuan Desert vascular flora - Villarreal-Quintanilla, José A.; Bartolomé-Hernández, Jenry A.; Estrada-Castillón, Eduardo; Ramírez-Rodríguez, Homero; Martínez-Amador, Silvia J. (Instituto de Ecología, A.C., 2017)
Background and Aims: Endemism is a common phenomenon in arid regions. In this study we reviewed the distribution of endemic plants in the Chihuahuan Desert (DCH), which includes portions of the states of Arizona, Chihuahua, Coahuila, Durango, Nuevo Leon, Nuevo Mexico, San Luis Potosi, Tamaulipas, Texas and Zacatecas.Methods: A database was set up summarizing the information on the restricted species from the DCH. The following types of endemism were considered: 1) endemics which are known from the study region only, 2) quasi-endemics with distribution mainly in the DCH and some populations in the neighboring areas, 3) micro-endemics which are restricted to one location, and 4) endemics of non-arid habitats in the area.Key results: A total of 826 taxa (including species, additional infraspecific taxa and hybrids) were determined to be endemics or quasi-endemics, representing 24.87% of the total flora. Of this, 560 are endemics, 165 quasi-endemics, 176 micro-endemics and 116 are from non arid habitats. The families with the most endemics are Cactaceae (141 species), Asteraceae (106), Boraginaceae (34) and Brassicaceae (31), that represent 46.2% of the total. The genera with the highest taxa numbers are Coryphantha (24), Echinocereus (14), Mammillaria (15), Turbinicarpus (15). Nine genera are exclusive to the DCH. The dominant biological forms are perennial herbs and shrubs, frequently distributed in the xeric shrubland. The endemic distribution is heterogeneous, with a density index of 0.128 species/km2. Coahuila has the largest number of elements (31.15%).Conclusions: It is suggested to continue the protection of Cuatro Ciénegas, and portions of Brewster, as well as the Sierras La Madera and El Carmen. Sierras de Parras, La Paila and Jimulco, and Concepción del Oro and Presidio, are proposed as conservation areas, as they concentrate a large number of endemic species.